PERLINDUNGAN HUKUM ATAS CIPTAAN LOGO PROVINSI PAPUA BARAT MENURUT UNDANG-UNDANG HAK CIPTA : Legal Protection Of The Creation Of The West Papua Province Logo According To Copyright Law - Izzah Balqies; Suci Lestari (Reformasi Hukum Trisakti, 2024)
The West Papua Province logo drawn by Pieter Mambor as an order from the Government of West Papua Provincial, Abraham Octavianus Atururi. However, the West Papua Provincial Government does not provide compensation to Pieter Mambor as the creator of the logo image. The main problem in this articles is how is the legal protection of the creation of the West Papua Province logo based on Law No. 28 of 2014 on Copyright? and whether the decision of the Makassar Commercial Court Number: 3/Pdt.Sus-HKI/Cipta/2022/PN Niaga Mks is accordance Law No. 28 of 2014 on Copyright? This research is normative type, descriptive nature, the main data is secondary data supported by interviews, data collection methods with literature studies, analyzed qualitatively and conclusions are drawn using deductive logic. The result of the research is the legal protection of the creation of the West Papua Province logo which is included in the category of fine art images regulated in Article 40 paragraph (1) of the UUHC and Decision 3/Pdt.Sus-HKI/Cipta/2022/PN Niaga Mks is not accordance with Article 9 paragraph (2) of Law No. 28 of 2014 concerning Copyright. The conclusion is that the logo of Papua province is included in the creation protected by copyright.